Knowledge, attitude, and practice of influenza vaccineamong health-care employees in Sultan Bin Abdulaziz Humanitarian City - Mariam H Alghamdi; Sulaiman Abdullah Alshammari (Wolters Kluwer Medknow Publications, 2020)
Objectives: This study aimed to investigate the knowledge, attitudes, and practices (KAP) of health-care employees (HCEs) in Sultan Bin Abdulaziz Humanitarian City (SBAHC) toward influenza vaccine. Methodology: We conducted this cross-sectional study between November and December 2018. The study population included all HCEs. We recruited eligible participants through stratified random sampling. Data collection was done using a validated questionnaire, comprising 19 questions and designed to explore the KAP of influenza vaccine among HCEs. Results: A total of 391 HCEs completed the electronic questionnaire. Overall, 66% of them had received the influenza vaccine and 44.8% of them had received the vaccine from SBAHC. The number of participants who reported direct involvement with patient care was 292 (74.7%). The primary reasons attributable for not receiving the influenza vaccine at all over the past years ranged from a belief that it was not effective, to the unavailability of the vaccine during the night shift. The primary reasons for not receiving it annually, among those who had been vaccinated at least once in the same period, ranged from lack of time to being away during the vaccination campaigns. Participants who were planning to get the vaccine in the present year accounted for 30.7% of the sample. Conclusion: The low number of participants intending to get the vaccine in the present year can be attributed to inadequate knowledge, false beliefs, and fears regarding the vaccine efficacy and safeness. An extensive campaign aimed at promoting vaccination is recommended. Although physicians are quite clear about the importance of vaccine, aggressive educational campaign to increase vaccination rate is still needed for nurses, allied health professionals, and support staff.